Is Leopoldamys neilli (Rodentia, Muridae) a synonym of Leopoldamys herberti? A reply to Balakirev et al. (2013) - Latinne, Alice; Chaval, Yannick; Waengsothorn, Surachit; Rojanadilok, Prateep; Eiamampai, Krairat; Sribuarod, Kriangsak; Herbreteau, Vincent; Morand, Serge; Michaux, Johan R. (Zootaxa, 2013)
Recently, Balakirev et al. (2013) presented a taxonomic revision of the genus Leopoldamys based on phylogenetic analyses. They identified five main Leopoldamys genetic lineages and suggested to rename several of them. According to these authors, the genetic lineage previously thought to belong to L. edwardsi (lineage L1) should be assigned to L. revertens while L. neilli (lineage L2) should be considered as a junior synonym of L. herberti. Using molecular and morphological data from a large sampling of Leopoldamys specimens, the aim of the present study was to investigate the taxonomic status of L. herberti and L. neilli. This study reveals that, contrary to Balakirev et al.’s statement, both genetic lineages L1 and L2 occur in Nakhon Ratchasima Province, close to the type locality of L. herberti. We also show that the external measurements and color pattern of L. herberti are highly similar to those of L1 specimens but are not consistent with the morphology of L2 specimens. Therefore these results strongly suggest that L. herberti should be assigned to the genetic lineage L1. Consequently L. neilli should not be considered as a junior synonym of L. herberti and this study confirms that the appropriate name of the genetic lineage L2 is L. neilli. Moreover, as our results show that L. herberti should be assigned to the lineage L1, this name has nomenclatural priority over L. revertens, the species name suggested by Balakirev et al. (2013) for this lineage.